Magnetic and non-magnetic AGB mixing for s-processing - Busso Maurizio (EPJ Web of Conferences, 2023)
I outline a few features of recent models for the formation of the neutron source 13C(α,n)16O in low mass stars (1 ≲ M/M⊙ ≲ 3, LMS ) ascendingfor the second time the Red Giant Branch, generally called Asymptotic Giant Branch, or AGB stars. I also briefly outline the nucleosynthesis results obtained trough them. The mentioned models consider the physical structure below the frequent downward extensions of the convective envelope into the He-intershell (the so-called third dredge-up or TDU episodes). There, the conditions are such that the occurrence of further mixing is strongly facilitated, due to the minimal temperature gradient. A way to induce proton mixing from the envelope (certainly not the only one) arises whenever the ambient magnetic fields expected for LMS promote the buoyancy of strongly magnetized flux tubes. I review some characteristics of the ensuing mixing episodes, mentioning how different hydrodynamical processes might yield similar effects, thus encouraging stellar physicists to verify in more detail this possibility.